The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1095/biolreprod.103.015446
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Steroidogenic Potential of Ovarian Cells of the Brushtail Possum (Trichosurus vulpecula)1

Abstract: The ovary of the brushtail possum (Trichosurus vulpecula) secretes steroids; however, little is known about the identity of the steroidogenic cells in the ovary. The aim of the present study was to determine the identity of the ovarian cell types expressing mRNAs encoding proteins important for steroidogenesis and determine at what stage of follicular development they are expressed. The genes examined were those for steroidogenic factor-1 (SF-1), steroidogenic acute regulatory protein (StAR), cytochrome p450 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…5). It is reported that P450 aromatase was expressed in the granulosa cells in mammalian species [14][15][16] with a few exceptions [17,18]. In the ovary of chickens, however, it is reported that immunoreactivity for P450 aromatase was absent in the granulosa cell layer but was present in the theca cell layer [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5). It is reported that P450 aromatase was expressed in the granulosa cells in mammalian species [14][15][16] with a few exceptions [17,18]. In the ovary of chickens, however, it is reported that immunoreactivity for P450 aromatase was absent in the granulosa cell layer but was present in the theca cell layer [19].…”
Section: Discussionmentioning
confidence: 99%
“…Reptilia are the only animal class belonging to both ectotherms and amniotes, and Aves are evolved from reptiles by one order. P450 aromatase is expressed in the granulosa cell layer of most mammalian species, such as humans [14], mice, rats [15], and brushtail possums [16], although in the ovary of pigs, it was expressed in not only the granulosa cell layer but also the theca cell layer [17], and in that of the tree shrew, it was expressed only in the thecal cell layer [18]. Unlike most mammalian species, P450 aromatase is expressed in the thecal cell layer of the chicken ovary [19].…”
Section: Introductionmentioning
confidence: 99%
“…There are some major differences in ovarian function in the possum compared with mono-ovulatory eutherian species. In particular, the steroidogenic capability (Whale et al 2003), gonadotrophin dependency and the expression of LH receptors (Eckery et al 2002) of granulosa cells occurs in follicles at a much earlier stage of development in the possum. Expression of LH receptors was first observed in theca interna at the time of antrum formation in possums (Eckery et al 2002) and many eutherian mammals (Bao & Garverick 1998, McNatty et al 1999, and is thought to be indicative of steroidogenic capability.…”
Section: Introductionmentioning
confidence: 99%
“…Prl has also been implicated in both parturition (Hearn 1974) and maintenance of embryonic diapause (Hearn 1974, Curlewis et al 1986) in several marsupial macropodid species, thereby suggesting a role in luteal function in marsupials. The widespread expression of Prl receptor mRNA (L Haydon & DC Eckery, unpublished observations) in those ovarian cell types that also express mRNA for steroid acute regulatory protein, P450 side-chain cleavage, 3b-hydroxysteroid dehydrogenase, and P450 aromatase (Eckery et al 2002, Whale et al 2003 in the brushtail possum implies that Prl plays a significant role in ovarian function and in particular steroidogenesis in this species. The recent development of a homologous Prl RIA for measuring Prl in brushtail possums (Crawford et al 2005) has enabled the endogenous secretory patterns of Prl during lactation, the oestrous cycle and throughout the breeding and non-breeding seasons to be elucidated for the first time in this species.…”
Section: Introductionmentioning
confidence: 99%